Exploring potential antidiabetic and anti-inflammatory flavonoids from Euphorbia humifusa with an integrated strategy - Rakotondrabe, Tojofaniry Fabien; Fan, Minxia; Guo, Mingquan (Frontiers in Pharmacology, 2022)
Euphorbia humifusa Willd, a monoecious annual plant, native to Eastern Asia, has been traditionally attributed to the treatment and prevention of miscellaneous diseases, including diabetes mellitus and its associated complications. Earlier studies have supported this species’ pharmacological efficacies including its antibacterial, antidiabetic, and anti-inflammatory properties. Even so, the underlying bioactive components with their mechanisms of action associated with its antidiabetic and anti-inflammatory effects remain elusive. The preamble in vitro assessments of the crude extract and its different fractions revealed that the n-butanol fraction (EHNB) exhibited the best activity, which was subsequently subjected to a rapid screening of candidate ligands through bio-affinity ultrafiltration with the two enzyme targets: α-glucosidase (α-Glu) and cycloxygenase-2 (COX-2) combined with UPLC/QTOF-MS. As a result, 7 compounds were identified from EHNB, among them, vitexin and astragalin were screened out as the most active ligand compounds. Vitexin showed great specific binding (SB) affinity values of 1.26 toward α-Glu and 1.32 toward COX-2, while astragalin showed 1.32 and 1.36, respectively. The docking simulation results exhibited strong interactions of vitexin and astragalin with the key residues of the enzyme targets, suggesting their possible mechanisms of action. The in vitro antidiabetic validation revealed noticeable half-maximal inhibitory effects (IC50) of 36.38 ± 3.06 µM for vitexin and 42.47 ± 4.13 µM for astragalin, much better than that of the positive drug acarbose (109.54 ± 14.23 µM). Similarly, these two compounds showed the inhibitory activity against COX-2 with the half-maximal inhibitory effects (IC50) at 27.91 ± 1.74 µM and 49.05 ± 1.49 µM, respectively. Therefore, these two flavonoid compounds (vitexin and astragalin) were speculated as potential antidiabetic and anti-inflammatory compounds from E. humifusa. Taken together, the integrated strategy applied to E. humifusa led to the fast identification of two potential double-acting flavonoids and enlightened its antidiabetic and anti-inflammatory uses. Besides these findings, the integrated strategy in this study could also be used to facilitate the rapid discovery and development of active candidates from other traditional herbal medicines against multi-drug targets and to aid in revealing their mechanisms of action for their traditional uses.